RANCANG BANGUN BUCK-BOOST CONVERTER SEBAGAI CHARGER BATERAI CONTROLLER BERBASIS PWM DENGAN SUMBER PHOTOVOLTAIC - Wibowo, Aldi; Huda, Abil (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2024)
Charging the battery by supplying electric current continuously. Charging is stopped when the battery voltage has reached the maximum voltage. If the battery has reached its maximum voltage but charging is still carried out, it will cause losses, namely the waste of electrical energy, to prevent damage to the battery, a controller known as a charger controller is needed. The main function of the charger controller is to maintain the state of the battery by preventing excessive current and voltage distribution. This research produces a system that can increase and decrease the voltage as desired by using a buck-boost converter circuit as a means of stabilizing the output voltage supplied to the battery with a measured voltage of 13.01 V and a current of 3.64 A.